SNOW AND ICE PROPERTIES AS RELATED TO ROADS AND RUNWAYS IN ANTARCTICA. - Abele,Gunars; Frankenstein,Guenther (1967)
Dynamic tests were performed to determine the Young's modulus of sea ice, derived from longitudinal wave velocities measured with a soniscope. Static tests consisted of standard ring tensile strength and simple beam or flexural strength tests. The strength data were plotted on a base of the brine volume for each test. The test results indicate that the annual sea ice at McMurdo Sound is capable of supporting cargo type aircraft. Snow runways capable of supporting a C-130 aircraft on wheels and providing marginal support to a C-121 can be constructed either with the Peter plow or with the pulvimixer. However, the runway would be reliable only during comparatively low temperatures (< -15C). Peter snow miller processing and bulldozer compaction methods appear to be feasible for effective depth processing and compaction of high strength snow pavements. The criteria for support of various types of aircraft on a snow runway are presented. (Author)